Association between high visceral fat area and postoperative complications in patients with Crohn's disease following primary surgery. (2nd February 2016) - Ding, Z.; Wu, X.‐R.; Remer, E. M.; Lian, L.; Stocchi, L.; Li, Y.; McCullough, A.; Remzi, F. H.; Shen, B.
Abstract: Aim: The aim of this study was to determine the association between visceral fat area (VFA) on CT and postoperative complications after primary surgery in patients with Crohn's disease (CD). Method: Inclusion criteria were patients with a confirmed diagnosis of CD who had preoperative abdominal CT scan. The areas of total fat, subcutaneous fat and visceral fat were measured using an established image‐analysis method at the lumbar 3 (L3) level on CT cross‐sectional images. Visceral obesity was defined as a visceral fat area (VFA) of ≥ 130 cm 2 . Clinical variables, intra‐operative outcomes and postoperative courses within 30 days were analysed. Results: A total of 164 patients met the inclusion criteria. Sixty‐three (38.4%) patients had postoperative complications. The mean age of the patients with complications (the study group) was 40.4 ± 15.4 years and of those without complications (the control group) was 35.8 ± 12.9 years ( P = 0.049). There were no differences in disease location and behaviour between patients with or without complications ( P > 0.05). In multivariable analysis, VFA [odds ratio (OR) = 2.69; 95% confidence interval (CI): 1.09–6.62; P = 0.032] and corticosteroid use (OR = 2.86; 95% CI: 1.32–6.21; P = 0.008) were found to be associated with postoperative complications. Patients with visceral obesity had a significantly longer operative time ( P = 0.012), more blood loss ( P = 0.019), longer bowel resection length ( P = 0.003), postoperative ileus ( P = 0.039) and a greater number of complications overall ( P < 0.001). Conclusion: High VFA was found to be associated with an increased risk for 30‐day postoperative complications in patients with CD undergoing primary surgery.